ANALYZING THE EFFECTIVENESS OF E-COMMERCE MARKETPLACE COUPON IN THE CULINARY INDUSTRY: A CASE STUDY OF DAGO RESTAURANT JAKARTA - Iswindiari Putri Utami, Anggita
New culinary industry opportunities always appear created by entrepreneurs. There will always be many entrepreneurs who enter this industry because the need for food is a basic need for all humans. At present, the culture of the Indonesian people has also changed. Indonesian people are easy to accept and adapt to various types of food. This potential is a target for foreign parties who want to invest in Indonesia. Several foreign restaurants have been found in Indonesia, one of which is DaGo Restaurant Jakarta. Introducing the restaurant, DaGo Restaurant Jakarta does not want to be out of date so DaGo Restaurant Jakarta uses technology assistance, by using the e-commerce marketplace namely Lakupon. However, in its implementation, collaboration between DaGo Restaurant Jakarta and Lakupon did not go well. The function of DaGo Restaurant Jakarta using Lakupon is to increase customer traffic. However, DaGo Restaurant Jakarta lost its revenue potential because the use of Lakupon vouchers did not reach the target. Therefore DaGo Restaurant Jakarta asks whether the use of the e-commerce marketplace is effective for its business. But apparently, this is because not many people know about e-commerce marketplace called Lakupon. So from there DaGo Restaurant Jakarta also had to decide how to increase their customer traffic. The purpose of this study is to select a new e-commerce marketplace for the DaGo Restaurant Jakarta which is analyzed using the Analytic Hierarchy Process (AHP). For the results FGD on 14 respondents to determine the criteria at AHP, 6 criteria were found namely attractive promotion, user interface, ease and security of transaction, credibility, user friendly, and variety of products. After surveying 104 respondents, the results obtained through AHP that Fave is the best choice as a new e-commerce marketplace with a weight of 0.457 compared to other candidates, namely Zomato with a weight of 0.352 and Eatigo with a weight of 0.191. This shows that Fave can be used to increase customer traffic at DaGo Restaurant Jakarta.